Artificial Intelligence and English Learning: A Narrative Review - Artha, Bhenu; Bahri; Niken Permata Sari; Utami Tunjung Sari; Antonius Satria Hadi; Cahya Purnama Asri; Elang Perwira Manggala Seta (CV. Kalimasada Group Profesional, 2024)
English language learning is undergoing a profound transformation with the advent of digital technology and Artificial Intelligence. This research, that conduct by narrative review method, will aim to address these gaps by synthesizing findings from the last decade of research and providing a comprehensive understanding of the current trends, challenges, and future directions in the use of AI for English language learning. Most existing studies focus on the efficacy of specific AI tools, with limited attention given to long-term effects on learners' language proficiency, retention, and socio-cultural competence. Additionally, much of the research to date has concentrated on English as a foreign language, with less emphasis on how AI can support multilingualism or the learning of English as a second language in diverse sociocultural contexts. Furthermore, there is a lack of studies that explore the ethical, cultural, and pedagogical implications of widespread AI adoption in language education, particularly in non-Western contexts. This study contributes valuable insights into the evolving landscape of the use of AI in English learning, highlighting both the promising potential and the challenges of integrating GenAI technologies. Suggestions for further research are to conduct empirical research on the concepts in this study.